The improvement of the aerobic capacity of young soccer players using the aerobic step with soccer elements - Dalip, M.; Imetovska, A.; Imetovska, L.; Rexhepi, F.; Saiti, B.; Ademi, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
It is very important as a coach of young players to be aware of the players` development stage and understand how the youth players can be trained not to impair their development. (Bangsbo, J. 2007). Children are not small adults and should definitely not to be trained in the same way as adults. (Bangsbo, J. 2007). With this kind design of training process, we can solve two tasks (motor and functional ability) simultaneously during the same training. The purpose of this study was to examine step aerobic exercise on aerobic capacity in young soccer players. Methods In this study, participants were U-17 young soccer players (16.7±0,3; height 172±7.2 cm; weight 67±4.7 kg; YOYOIE2-I Max. running distance 1920 m and minimum running distance its 240m., mean its 125±479m. The YO YO intermmittent endurance test 2 participants have a short active break period during the test (5 seconds). The players were measured intermittent endurance ability, using the YO YO intermittent endurance 2 test YOYOIE2. During the competition period (12 weeks), we had 2 sessions of aerobic step test per week, each session have 45 minute duration. In the aerobic step exercise, we used music with low, moderate and high intensity tempo Results & Discussion In the final test of YOYOIE2, the maximum running distance was 2400m, minimum running distance was 560m and the mean value its 154±483m. Between Initial and Final measurement of YOYOIE2, there was a significant difference P<0.05. After the 12 week program of aerobic step with rhythmic music, young players improved the running distance 290±303 m. Conclusion The aerobic step training sessions are one of the best solutions for training methods to improve aerobic capacity in young soccer players. (Shriener, 2000). After using the aerobic step program, we found a significant increase of aerobic capacity of young soccer players.